Microbiological monitoring for assessment of bathing in a beach at North of Santa Catarina - Baucke, Alex Sandro; Zambão, Patrícia Hüther; Serbent, Maria Pilar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The human actions arising from influx of visitors in coastal regions may be associated to public health problems and negative effects to the environment. In this sense, microbiological analysis of water samples were developed on a beach in north Santa Catarina, located in the municipality of Penha. To verify the sea water for contact primary to recreation and to have a monitoring data basis, the considerations made by environmental agency of State of Santa Catarina were analyzed complementarily. The study happened in November of 2014 and January/ March of 2015. The water collection it occurred on eight points along the Penha’s Beach. The points are salty water (sea) and wastewater disposal on the sand. Throughout the study, microbiological contamination was observed due to the presence of Escherichia coli, an important indicator of fecal contamination, in the places where sampling of the water and exposed wastewater at the edge of the beach were performed. The results obtained showed discrepancy in values of E. coli between points and collected periods. Thus, it is suggested the need for a larger number of samples for monitoring water quality, especially at the time with great flow of tourists in order to avoid problems of public health as a water borne diseases. Finally, it is understood that this work can not characterize properly the bathing conditions, due to the short period of study. However, the joint work of environmental agencies and universities may lead to better information regarding bathing conditions at coastal areas available to the public.